Immunohistochemical detection of C9orf72 protein in frontotemporal lobar degeneration and motor neurone disease: patterns of immunostaining and an evaluation of commercial antibodies. Issue 1 (2nd January 2018) - Davidson, Yvonne S.; Robinson, Andrew C.; Rollinson, Sara; Pickering-Brown, Stuart; Xiao, Shangxi; Robertson, Janice; Mann, David M. A.
Abstract: We have employed as 'gold standards' two in-house, well-characterised and validated polyclonal antibodies, C9-L and C9-S, which detect the longer and shorter forms of C9orf72, and have compared seven other commercially available antibodies with these in order to evaluate the utility of the latter as credible tools for the demonstration of C9orf72. C9-L and C9-S antibodies immunostained cytoplasmic 'speckles', and the nuclear membrane, respectively, in cerebellar Purkinje cells of the cerebellum in patients with behavioural variant frontotemporal dementia (bvFTD) with amyotrophic lateral sclerosis (ALS), and in patients with ALS alone. Similar staining was seen in Purkinje cells in healthy control tissues and in other neurodegenerative disorders, and in pyramidal cells of CA4 and dentate gyrus of hippocampus. However, in the spinal cord there was little cytoplasmic staining with C9-L antibody. C9-S antibody immunostained the nuclear membrane of anterior horn cells in healthy neurons. In patients with bvFTD + ALS, or ALS alone, this C9-S nuclear staining was redistributed to the plasma membrane. In those patients with bvFTD + ALS or ALS bearing an expansion in C9orf72, none of the commercially available antibodies detected TDP-43 inclusions in anterior horn cells, nor were dipeptide repeat proteins demonstrated. Five of the commercial antibodies provided immunohistochemical staining patterns similar in morphological appearance to the in-house C9-L antibody, but distinct from C9-S antibody. However, only three showed sufficient specificity and intensity of staining for C9orf72 at acceptably low concentrations, to make them of practical value and sufficiently reliable for the detection of at least the longer form of C9orf72 protein.